AKTUALISASI PEDIDIKAN KARAKTER DALAM PENGEMBANGAN REVOLUSI MENTAL BERBASIS ADIWIYATA DAN MULTIKULTURAL - suhardi suhardi (STKIP PGRI Jombang, 2018)
Mental revolution of education requires efforts to print educated human beings by having the motivation to meet the standards of achievement excellence, such as ethos of progress, ethics, achievement motivation, discipline, optimistic, productive, innovative and active views. This can be implemented with character education. Character education is one of the soft skill tools that can be integrated in learning in each subject. Learning activities using an active learning approach have a strategic role in instilling national character values so that students are able to behave and act on values that have become their personality. The purpose of this study was to find and analyze about: 1) Implementation of Character Education to Build Adiwiyata-Based Mental Revolution and Multiculturalism; 2) Implementation of Character Education to Build Mental Revolution in Organizational Culture. This study uses a qualitative approach with phenomenological naturatistics (phenomenology approach), with a descriptive type of case study research design. Data were analyzed using data analysis techniques: data reduction, data analysis and conclusions. The results of the study are: The application of character education to develop a mental revolution can be started from the character of building the environment. Environmental character is very important for individual development. The implementation of character education in building a mental revolution can emphasize the internalization of multicultural values and Adiwiyata which in the end will form a loving environmental awareness and foster a spirit of tolerance.